DAMPAK PENYIMPANGAN IKLIM TERHADAP PERUBAHAN KARAKTERISTIK HUJAN DI PATUK, GUNUNGKIDUL (EFFECT OF CLIMATE DEVIATION ON CHANGE OF RAINFALL CHARACTERISTIC IN PATUK, GUNUNG KIDUL) Rajiman Rajiman - Rajiman, Rajiman (Jurnal Ilmu-Ilmu Pertanian, 2005)
The Climate had response of importance on plant growth and production. The climate elements to effecting to plant is rainfall (distribution and total). Rainfall of effecting to reckoning has distribution in agriculture. The objective of this research is : to look of effect El Nino and La Nina on characteristic and change of rainfall in Patuk Gunung Kidul. This study used descriptive design to facta and fenomena response. Data collected from rainfaal station in Putat (1980-2002), then analized an interprestation of climate deviation. The result research are : The rainfall ofter 1990 heigher from old years. Effict from El Nino of strong showed dry season leight duration (2-5 decade). Effect of ln Nina on wet season of leight duration (3 decade month of Oktober - 2 decade month of Juni).